Chlorella vulgaris ameliorates oxidative stress and improves the muscle regenerative capacity of young and old Sprague-Dawley rats - Zainul Azlan, Nurhazirah; Mohd Yusof, Yasmin Anum; Makpol, Suzana (MDPI, 2020)
Muscle atrophy in ageing is a multifactorial degenerative process impacted by cellular ageing biology, which includes oxidative stress. Chlorella vulgaris is a coccoid green eukaryotic microalga rich in antioxidants. The aim of this study was to determine the effect of C. vulgaris in ameliorating oxidative stress, thus elucidating its mechanism in improving muscle mass, strength and function in young and old rats. Fifty-six male Sprague-Dawley (SD) rats aged 3 months (young) and 21 months (old) were divided into three groups: Group 1 (control) was given distilled water; Group 2 was treated with 150 mg/kg body weight (BW) of C. vulgaris; and Group 3 was treated with 300 mg/kg BW of C. vulgaris for three months. Grip and muscle strength and muscle integrity were determined on days 0, 30, 60, and 90 of treatment. Urine and blood were collected on days 0 and 90 of treatment for oxidative stress marker determination, while the gastrocnemius muscles were collected for muscle oxidative stress analysis. Increased grip strength of the front and hind paws was observed in young C. vulgaris-treated rats on days 30, 60, and 90 compared to the untreated control on the same days (p < 0.05). There was a significant increase in lean bone mineral content (BMC) in young rats treated with 300 mg/kg BW C. vulgaris compared to untreated rats on days 30 and 60. The fat mass was significantly decreased in young and old C. vulgaris-treated rats on day 90 compared to the untreated control. The total path was significantly increased for old rats treated with 300 mg/kg BW C. vulgaris on days 60 and 90 compared to day 0. Young and old C. vulgaris-treated rats demonstrated a significant decrease in urinary isoprostane F2t and plasma creatine kinase-MM (CKMM) compared to the control on day 90. A significant decrease in malondialdehyde (MDA) and 4-hydroxyalkenal (HAE) levels were observed in young and old rats treated with C. vulgaris. C. vulgaris improved the muscle mass, strength, and function in young and old rats. This effect could be due to its potency in ameliorating oxidative stress in the skeletal muscle of young and old rats.